Integrating biomedical HIV prevention in schools: Protocol for a systematic review of interventions for adolescent girls and young women in sub-Saharan Africa - Cecilia Afua Lodonu-Senoo; Lily Ogyiri; Kwasi Torpey; Francis Zotor (PLoS ONE, 2026)
Introduction Despite global progress in reducing HIV incidence, adolescent girls and young women in sub-Saharan Africa remain disproportionately affected. Biomedical HIV prevention tools such as pre-exposure prophylaxis, condoms and HIV testing are effective but underutilized, especially within facility-based models. Schools represent consistent and scalable contact points for reaching adolescent girls and young women, yet evidence on the feasibility, accessibility and effectiveness of school-based biomedical HIV prevention interventions remains limited. Objective This systematic review aims to synthesize evidence on how school-based programs implement, deliver and achieve outcomes in HIV prevention interventions involving pre-exposure prophylaxis, condom and HIV testing for adolescent girls and young women in sub-Saharan Africa. Materials and methods This review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. Eligible studies will include randomized and non-randomized trials and qualitative research published between January 2015 and December 2025. Databases to be searched include PubMed, Embase, PsycINFO, CINAHL and the African Index Medicus, together with relevant grey literature sources (WHO, UNAIDS, UNICEF and PEPFAR). Two reviewers will independently screen titles, abstracts, and full texts, extract data, and assess risk of bias using appropriate tools. Quantitative data will be synthesized using meta-analysis where feasible, while qualitative findings will undergo thematic synthesis. Outcomes of interest include the feasibility, accessibility, and effectiveness of school-based HIV prevention interventions. Discussion This review will provide a comprehensive synthesis of evidence on biomedical HIV prevention interventions delivered in school settings for adolescent girls and young women in sub-Saharan Africa. Findings will highlight implementation process, barriers, facilitators and equity considerations. Trial registration number: PROSPERO CRD420251249595